2014
DOI: 10.1093/neuonc/nou102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meriolins, a new class of cyclin-dependent kinase inhibitors, on malignant glioma proliferation and neo-angiogenesis

Abstract: Meriolins, and meriolin 15 in particular, exhibit antiproliferative and proapoptotic activities on both glioma and intratumoral endothelial cells, constituting key promising therapeutic lead compounds for the treatment of glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…GBM xenograft growth was evaluated after subcutaneous (s.c.) injection, into the flank of 4-week-old male nude mice, of GBM xenografts (GBM_SC1 or GBM_SC2) as described previously (30). When the first tumor reached the size of approximately 1,500 mm 3 , mice were euthanized.…”
Section: Xenograft Transplantation In Micementioning
confidence: 99%
“…GBM xenograft growth was evaluated after subcutaneous (s.c.) injection, into the flank of 4-week-old male nude mice, of GBM xenografts (GBM_SC1 or GBM_SC2) as described previously (30). When the first tumor reached the size of approximately 1,500 mm 3 , mice were euthanized.…”
Section: Xenograft Transplantation In Micementioning
confidence: 99%
“…Selectivity of expressed transmembrane proteins across the BBB enhanced the cross-membrane transport and delivery to active sites in human neuroglioma. However, increased adenosine triphosphate ATP in human H4 neuroglioma cells increased alpha synuclein, and inhibited neurogenesis [15]. Intracellular protein expression of meriolins on arctic medicinal marine invertebrates inhibited cyclin-dependent kinase, decreased ATP [16].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, synthetic hybrid molecules called meriolins were derived from meridianins, and shown to induce apoptosis in neuroblatoma SH-SY5Y cells [ 141 ]. Comparative analysis of a panel of meriolins showed that meriolin-15 significantly inhibited proliferation and induced apoptosis in GBM cells [ 142 ].…”
Section: Natural Products Effecting Gbm Cell Proliferation and Apoptomentioning
confidence: 99%